Brief Report: Stigma and HIV Care Continuum Outcomes Among Ethiopian Adults Initiating ART. (1st December 2017) - Hoffman, Susie; Tymejczyk, Olga; Kulkarni, Sarah; Lahuerta, Maria; Gadisa, Tsigereda; Remien, Robert H.; Melaku, Zenebe; Nash, Denis; Elul, Batya
Abstract : Background: Stigma harms the mental health of HIV-positive individuals and reduces adherence to antiretroviral therapy (ART), but less is known about stigma and other outcomes across the HIV care continuum. Methods: Among 1180 Ethiopian adults initiating ART at 6 urban HIV clinics, we examined the relationship of internalized, anticipated, and enacted stigma to HIV care-related outcomes ascertained by interview (repeat HIV-positive testing, provider vs. self-referred testing, missed clinic visit before ART initiation, eagerness to begin ART), and by abstraction of routinely collected clinical data (late ART initiation, 3-month gap in care following ART initiation). Logistic regression was used to assess the association of each type of stigma with each outcome, adjusting for potential confounders. Results: Scoring higher on each stigma domain was associated with 50%–90% higher odds of repeat HIV-positive testing. High internalized stigma was associated with higher odds of provider vs. self-referred test [adjusted odds ratio (aOR)high vs. low : 1.7; 95% confidence interval (CI): 1.3 to 2.2]. Higher anticipated stigma was associated with lower eagerness to begin ART (aORhigh vs. low : 0.55; 0.35–0.87; aORmedium vs. low : 0.45; 95% CI: 0.30 to 0.69). Any enacted stigma was associated with higher odds of a missed visit (aORany vs. none 1.8; 1.2–2.8). Stigma was not associated with late ART-initiation or with a subsequent gap in care. Discussion and Conclusions: These findings provide further evidence of the importance of measuring and addressing stigma across the entire care continuum. Future work should test hypotheses about specific stigma domains and outcomes in prospective intervention or observational studies.